Agricultural Innovations in Bangladesh - Understanding the Adoption-Diffusion Process - Rabbanee, Fazlul; Quaddus, Mohammed; Jackson, Elizabeth (2019)
Bangladesh has made remarkable achievements in reducing poverty with admirable GDP growth over the last decade. The government has invested huge resources in the development of home-grown agricultural innovations. However, the sustainability of domestic food grain production remains an issue and technological innovations that have been adopted by farmers are not always those funded by the government. Unfortunately, there is no in-depth assessment of whether the rural farmers of Bangladesh adopt local or imported agricultural innovations. Besides, the key factors facilitating and inhibiting the adoption of agricultural innovation and how to deal with these problems are still unknown. The key purpose of this research is to better understand the adoption-diffusion process of agricultural technology. An understanding of the adoption-diffusion process will help to find out why (or why not) the agricultural value chain participants adopt local vs imported agricultural innovations. This paper reviews existing knowledge on the adoption-diffusion process, explores the factors that influence the adoption of the agricultural innovations, and identifies the attitudes of agricultural technology users of Bangladesh. Further, the paper shows that successful adoption of the agricultural technology contribute to the economic development of Bangladesh.